Synemon ignita sp. nov., a new sun moth species from southern Australia (Lepidoptera, Castniidae) - Kallies, Axel; Edwards, Ted; Young, Andy; Douglas, Fabian (Zootaxa, 2016)
Sun moths (Castniidae) constitute a family of day-flying moths that due to their slim bodies, broad and often richly coloured wings and clubbed antennae closely resemble butterflies. However, despite this superficial similarity, sun moths are not related to butterflies but belong to the diverse cossoid assemblage of lepidopterous families (Edwards et al. 1998). Until recently, Castniidae were assigned to the superfamily Sesioidea (Minet 1991). A molecular study by Mutanen et al. (2010), however, failed to find support for a close relationship of Sesiidae and Castniidae, resulting in the inclusion of both families in a larger concept of Cossoidea (Nieukerken et al. 2011). In contrast, Heikkil et al. (2015) who added considerable morphological data to DNA, recovered Sesioidea as monophyletic, with Sesiidae, Castniidae and Brachodidae as constituent families, yet with low support values. Thus, although the monophyly of Castniidae is well supported, the systematic position of this family is unresolved.